Q. 365.0( 1 Vote )

# Find the roots of the quadratic equation 2x2 - x - 6 = 0.

Given: 2x2 - x - 6 = 0

Using the splitting middle term - the middle term of the general equation is divided in two such values that:

Product = a.c

For the given equation a = 2 b = - 1 c = - 6

= 2. - 6 = - 12

And either of their sum or difference = b

= - 1

Thus the two terms are - 4 and 3

Sum = - 4 + 3 = - 1

Product = - 4.3 = - 12

2x2 - 4x + 3x - 6 = 0

2x(x - 2) + 3(x - 2) = 0

(x - 2) (2x + 3) = 0

x = 2 or x = - 3/2

Hence the roots of the given equation x = 2 or x = Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Get To Know About Quadratic Formula42 mins  Quiz | Knowing the Nature of Roots44 mins  Take a Dip Into Quadratic graphs32 mins  Foundation | Practice Important Questions for Foundation54 mins  Nature of Roots of Quadratic EquationsFREE Class  Getting Familiar with Nature of Roots of Quadratic Equations51 mins  Quadratic Equation: Previous Year NTSE Questions32 mins  Champ Quiz | Quadratic Equation33 mins  Balance the Chemical Equations49 mins  Champ Quiz | Quadratic Equation48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 